2013
DOI: 10.1167/iovs.13-12047
|View full text |Cite
|
Sign up to set email alerts
|

Topical Silver Nanoparticles Result in Improved Bleb Function by Increasing Filtration and Reducing Fibrosis in a Rabbit Model of Filtration Surgery

Abstract: In a rabbit model of filtration surgery, AgNPs are a reasonable alternative to MMC as adjunctive therapy. Compared to MMC, AgNPs result in an improved and sustained reduction of IOP and promote blebs with decreased fibrosis and ischemia as well as increased filtration despite a smaller overall size. This combination may offer an opportunity to promote long-term surgical IOP reduction with an improved complication profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…In addition, the FS can be used to monitor the progression of fibrosis with novel anti-fibrotic agents. 28 The present method has certain limitations for evaluation of blebs with strong inflammation and congestion. In our previous rabbit study, 14 we have seen no increase in phase retardation 0 days after surgery compared to 1 and 2 weeks after the surgery.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the FS can be used to monitor the progression of fibrosis with novel anti-fibrotic agents. 28 The present method has certain limitations for evaluation of blebs with strong inflammation and congestion. In our previous rabbit study, 14 we have seen no increase in phase retardation 0 days after surgery compared to 1 and 2 weeks after the surgery.…”
Section: Discussionmentioning
confidence: 94%
“…Other reports indicated survival rate ranged from 0% to 50% at various follow-up periods (from 4-6 weeks). 16,[37][38][39] From these results, it appears to be difficult to achieve greater than 90% bleb survival (human 1-year goal) at 3 months in a rabbit model of filtration surgery with MMC, because the wound healing reaction is more aggressive in rabbits than in humans. Accordingly, the results of experiment 2 indicate that a HPF with 0.5 lg PTX provided sustained IOP reduction and favorable bleb survival even after a long follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Using the rabbit model of glaucoma filtration surgery, Butler et al showed that topical silver nanoparticles (Ag-NPs) achieved an improved and sustained reduction in intraocular pressure, and led to blebs with decreased fibrosis and ischemia compared with MMC [ 71 ]. Ag-NPs have also been shown to accelerate wound healing after skin burns, with decreased scar tissue formation and anti-inflammatory effects [ 72 ].…”
Section: Nanoparticlesmentioning
confidence: 99%